2015
DOI: 10.1021/acs.est.5b03738
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Current and Future Roles of Particulate Organic Nitrates in the Southeastern United States

Abstract: Organic nitrates are an important aerosol constituent in locations where biogenic hydrocarbon emissions mix with anthropogenic NOx sources. While regional and global chemical transport models may include a representation of organic aerosol from monoterpene reactions with nitrate radicals (the primary source of particle-phase organic nitrates in the Southeast United States), secondary organic aerosol (SOA) models can underestimate yields. Furthermore, SOA parametrizations do not explicitly take into account org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
250
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(275 citation statements)
references
References 75 publications
(152 reference statements)
7
250
3
Order By: Relevance
“…These ELVOCs have been observed during both chamber and in situ measurements in Germany (Mutzel et al, 2015). Several studies showed the importance of nighttime SOA formation from MT via nitrate radical oxidation, resulting in the formation of organic nitrates (Pye et al, 2015;Bean and Ruiz, 2016;Xu et al, 2015;Nah et al, 2016). Pye et al (2010) showed the importance of reactive nitrogen and pointed out the fact that organic nitrate accounts for more than a half of the monoterpene oxidation products in the particle phase over the US.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These ELVOCs have been observed during both chamber and in situ measurements in Germany (Mutzel et al, 2015). Several studies showed the importance of nighttime SOA formation from MT via nitrate radical oxidation, resulting in the formation of organic nitrates (Pye et al, 2015;Bean and Ruiz, 2016;Xu et al, 2015;Nah et al, 2016). Pye et al (2010) showed the importance of reactive nitrogen and pointed out the fact that organic nitrate accounts for more than a half of the monoterpene oxidation products in the particle phase over the US.…”
Section: Introductionmentioning
confidence: 83%
“…Organic nitrates are formed where biogenic VOCs and anthropogenic NO x sources interact (Pye et al, 2015;Xu et al, 2015;Bean and Ruiz, 2016;Nah et al, 2016). We used here the parameterisation of Pye et al (2015) to account for the formation of organic nitrate compounds from the oxidation by OH and NO 3 of MT.…”
Section: Organic Nitrates Formation Mechanismmentioning
confidence: 99%
“…Next to the current 1-D VBS scheme, 2-D schemes have been developed, taking into account not only the saturation vapour pressure but also the O : C ratio (oxygenation state) (Donahue et al, 2011). In addition, the importance and pathways of reactive nitrogen were demonstrated by Pye et al (2010Pye et al ( , 2015. Reactive nitrogen is not yet taken into account.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…6). This suggests that isoprene OA formation may be only half of the value found by Kim et al (2015), implying that other sources such as terpenes may make more important contributions to OA (Pye et al, 2010(Pye et al, , 2015Xu et al, 2015).…”
Section: Implications For Surface Air Qualitymentioning
confidence: 92%